Vyjmenovaná slova s Radkou a Kájou a pejskem Ottou - Nováková, Andrea (Masaryk University Press, 2021)
Title in English: Listed words with Radka and Kája and dog Otto Illustrated textbook of listed words with regard to the needs of children with hearing impairment. The textbook was created as part of the student's final thesis in cooperation with the Department of Special Education at Masaryk University.